Management And Transition Mechanism Of Land PT. Kawasan Industri Wijayakusuma (Persero) Of Semarang City - Andhika Buana Prasadhana; Widya Putri Idayatama; Anis Mashdurohatun (Jurnal Akta, 2019)
The study "Mechanism of Transition Management and Land Rights PT Kawasan Industri Wijayakusuma/KIW (Persero) Semarang", aims: 1) To be able to know and analyze the pre-implementation process of managing the transition of land rights in PT. KIW (Persero) Semarang. 2) In order to determine and analyze the management process as well as implementation and post-implementation transition of land rights in PT. KIW (Persero) Semarang. 3) To examine and analyze the barriers that exist in the process of pre- to post-implementation management transition of land rights in PT. KIW (Persero) Semarang and the efforts of its solution.The results showed that: 1) the pre-implementation process of transition land rights there are still things that do not based procedures or norms that apply in the case of land acquisition. 2.a) the transition process of land rights especially those of the company of Persero/Liability Company (PT) with the usual transition land rights-related mechanisms making it different. 2B) post-implementation process was related to the Master Plan of PT. KIW Semarang in accordance with the Spatial Plan (RTRW) of Semarang. 3) The existence of barriers that occur and the impact on the transfer of land rights PT. KIW Semarang, which is still difficult to solve.Keywords: Management; Transfer of Rights Land Company.